Mechanism of interaction and removal of zinc with lignocellulosic adsorbents, closing the cycle with a soil conditioner - Kayranli, Birol (Journal of King Saud University. Science, 2021)
Batch experiments were performed to remove Zn2+ by adsorption process using organic residuals (pistachio, peanut, and almond) as an adsorbent. The adsorbents were characterized by FTIR spectra, SEM images, and elemental analysis. Optimum adsorption of Zn2+ was obtained at pH 6 with a contact time of 45 min at room temperature with 1.0 g adsorbents. The adsorption of Zn2+ was found to well describe Langmuir isotherm model and a pseudo-second-order rate equation. The maximum adsorption capacity of pistachio, peanut, and almond is as follows; 59.52 mgg-1, 54.64 mgg-1, and 51.81 mgg-1, respectively. Functional groups on shell surfaces can cooperate with metal ions in many ways such as electrostatic interaction, ion exchange, complex formation, and diffusion. This study has shown that pistachio, peanut, and almond shell can be used for reducing Zn2+ from aqueous solutions as an eco-friendly, low-cost adsorbent. The end-product containing organic compounds and zinc can be used as a soil conditioner. Furthermore, the usage of the organic shell as a sorbent for the capturing of zinc from contaminated water ensures both the technical advantage and cost-effectiveness for the sustainable environmental management concept.